The relationships between functional and dysfunctional impulsivity and aggression across different samples - Tous, Jordi; Vigil-colet, Andreu; Morales-vives, Fabia (The Spanish Journal of Psychology, 2008)
E. S. Barratt proposed the term impulsive aggression to define a kind of aggression that is characterized by acting without thinking because of high levels of impulsivity. Previous research using psychometric measures has shown that impulsivity and aggression are related as far as psychometric measures are concerned. Nevertheless, most of the research has been done with samples of university students. Our research tests whether this relationship is stable across different samples; university students, teenagers and workers. Our results show that impulsivity and aggression have a consistent pattern of relationships across these samples, with impulsivity being specially related to emotional and instrumental aspects of aggression. Furthermore, the effects of anger on aggression seem to show a pattern of relationship that depends on age, with a tendency to physical aggression in young people and verbal aggression in adults.